2023
DOI: 10.1183/23120541.00046-2023
|View full text |Cite
|
Sign up to set email alerts
|

Increasing airway obstruction through life following bronchopulmonary dysplasia: a meta-analysis

Abstract: Few studies exist investigating lung function trajectories of those born preterm, however growing evidence suggests some individuals experience increasing airway obstruction throughout life. Here we use the studies identified in a recent systematic review to provide the first meta-analysis investigating the impact of preterm birth on airway obstruction measured by the FEV1/FVC ratio.Cohorts were included for analysis if they reported FEV1/FVC in survivors of preterm birth (<37 weeks’ gestation) and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…Air ow obstruction is a common impairment associated with prematurity, particularly prevalent in patients diagnosed with BPD, and tends to persist into adulthood, as indicated by a recent meta-analysis [27]. This obstruction often arises from a mismatch between distal airway growth and lung volume, known as dysanapsis, resulting from disruptions in normal pulmonary development [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air ow obstruction is a common impairment associated with prematurity, particularly prevalent in patients diagnosed with BPD, and tends to persist into adulthood, as indicated by a recent meta-analysis [27]. This obstruction often arises from a mismatch between distal airway growth and lung volume, known as dysanapsis, resulting from disruptions in normal pulmonary development [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies suggest improved long-term respiratory outcomes in contemporary cohorts of preterm infants compared with earlier populations [18,34]. others show no differences [27,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advancements in the survival rates of extremely preterm infants, the prevalence of respiratory sequel, particularly BPD, remains high (1,2). Prior research indicates that patients diagnosed with BPD are at an increased risk of asthma and pulmonary function abnormalities compared to those without BPD (5,(19)(20)(21)(22). However, there is no established consensus on the impact of this condition on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The Respiratory Health Outcomes in Neonates (RHiNO) study has recently demonstrated that there are multiple spirometry phenotypes of PLD, including both fixed and reversible prematurity-associated obstructive lung disease (POLD), prematurity-associated preserved ratio with impaired spirometry (pPRISm) and dysanaptic spirometry patterns, which are differentially associated with early- and current-life factors, including BPD ( 6 ). There is an increasing concern that PLD may predispose an individual to the premature development of chronic obstructive pulmonary disease (COPD) in early adulthood ( 7 , 8 ), with implications for quality of life and life expectancy if lung function deficits continue to track into adulthood. Whilst much research focus has concentrated on the mechanism of respiratory morbidity in those with a history of BPD ( 9 , 10 ), it is increasingly apparent that there is a population of preterm-born subjects who develop PLD despite not having had a diagnosis of BPD in the neonatal period ( 3 , 11 ), with impaired spirometry, altered respiratory mechanics and reduced gas diffusion capacity ( 12 ).…”
mentioning
confidence: 99%